Pengembangan Media Pembelajaran Game Edukasi Quizalize untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Bahasa Indonesia - Kamiliya, Khansa; Nurjanah, Hifni Fitriah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this research is to develop valid and effective educational game learning media based on Quizalize, as well as to enhance the learning motivation of tenth-grade students at SMA Negeri 1 Jalaksana. The method used in this research is the ADDIE development model, which consists of five stages: analyze, design, development, implementation, and evaluation. The subjects of this research involve 30 students from class X-M-7. The development process begins with an analysis of student needs and the curriculum, followed by the design of media that includes creating biographical content, interface design, and developing interactive quizzes. Media validation is conducted by two experts, namely a content expert and a media expert, who provide assessments of the feasibility of the developed media. The results of the validation showed that the developed learning media meets the eligibility criteria with a percentage of 92% from material experts and 91% from media experts, categorized as very good. The analysis results indicated a significant increase in student learning motivation after using the Quizalize media, with the average motivation score rising from 70 to 85. The conclusion of this study is that the Quizalize-based educational game learning media developed is not only valid and feasible to use, but also effective in enhancing student learning motivation in the Indonesian language subject on biography material.